ESG Dimensions and Stock Return Volatility: Empirical Evidence from Shariacompliant Manufacturing Firms - Ghaida Aulia Purwantika; Hendi Rohendi; Mochammad Edman Syarief (Cv. Syntax Corporation Indonesia, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) dimensions on the stock price volatility of Sharia-compliant companies listed in the Indonesian Sharia Stock Index (ISSI) within the manufacturing sector over the period 2018–2024. This study employs a quantitative approach using panel data regression. ESG is measured based on sustainability report disclosures referring to GRI Standards, while stock price volatility is calculated using the standard deviation of stock returns. The results indicate that the Environmental dimension has a significant negative effect on stock price volatility, whereas the social dimension is only significant at the 10% level and the Governance dimension shows no significant effect. These findings suggest that the market does not respond to ESG as a unified construct, but rather selectively based on the relevance of each dimension to firm-level risk. In the context of the manufacturing sector, the environmental aspect is more dominant due to its direct association with operational risk.